2021
DOI: 10.4062/biomolther.2021.012
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Autophagy: Characteristic Features and Roles in Neuronal Pathophysiology

Abstract: Autophagy is an important degradative pathway that eliminates misfolded proteins and damaged organelles from cells. Autophagy is crucial for neuronal homeostasis and function. A lack of or deficiency in autophagy leads to the accumulation of protein aggregates, which are associated with several neurodegenerative diseases. Compared with non-neuronal cells, neurons exhibit rapid autophagic flux because damaged organelles or protein aggregates cannot be diluted in post-mitotic cells; because of this, these cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 135 publications
(167 reference statements)
0
15
0
Order By: Relevance
“…The UPR has been associated with many neurodegenerative diseases, and more detailed information on these associations can be found in reviews such as Hetz and Saxena, 2017, and Xiang et al, 2017 [ 41 , 42 ]. For the purposes of this section, we will discuss the role of the IRE1 pathway, ERS protein BiP, and autophagy in neurodegeneration, each of which relates to the KDEL receptors and has been implicated in neurodegeneration [ 42 , 43 , 44 ]. The IRE1 pathway, specifically, is implicated in Parkinson’s disease, Huntington’s disease, and amyotrophic lateral sclerosis (ALS) [ 42 ].…”
Section: Kdel Receptors Upr and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The UPR has been associated with many neurodegenerative diseases, and more detailed information on these associations can be found in reviews such as Hetz and Saxena, 2017, and Xiang et al, 2017 [ 41 , 42 ]. For the purposes of this section, we will discuss the role of the IRE1 pathway, ERS protein BiP, and autophagy in neurodegeneration, each of which relates to the KDEL receptors and has been implicated in neurodegeneration [ 42 , 43 , 44 ]. The IRE1 pathway, specifically, is implicated in Parkinson’s disease, Huntington’s disease, and amyotrophic lateral sclerosis (ALS) [ 42 ].…”
Section: Kdel Receptors Upr and Diseasementioning
confidence: 99%
“…The KDEL receptor’s function in ER protein retention is not the only role that might have neurodegenerative disease implications. KDEL receptors can also modulate autophagy which is impaired in some neurodegenerative diseases [ 44 ]. A study demonstrated that misfolded proteins, such as huntington (Htt) in Huntington’s disease, superoxide dismutase 1 (SOD1) in ALS, and α-synuclein (a-syn) in Parkinson’s disease, were all shown to increase KDEL receptor expression, and the knock down of KDEL receptors led to increased levels of the disease-related proteins.…”
Section: Kdel Receptors Upr and Diseasementioning
confidence: 99%
“…KDELRs were found upregulated/relocated in the ER in cerebral and myocardial ischemia [ 49 , 50 , 51 ], diabetes [ 52 , 53 ], and neurodegenerative diseases including Parkinson’s disease, Huntington’s disease, Pelizaeus–Merzbacher disease, as well as in amyotrophic lateral sclerosis (ASL) [ 35 , 40 , 54 , 55 , 56 ]. These neurodegenerative diseases share pathological ER stress leading to the accumulation of protein aggregates [ 40 , 54 ] and activation of the UPR, although aberrant autophagy has also been involved [ 57 ]. Upregulation of KDELRs could potentially be useful in neurodegenerative disease and after an ischemic attack to retain ER proteins and ensure the protective effects exerted by factors such as cardiomyokine cerebral dopamine neurotrophic factor (CDNF) or mesencephalic astrocyte-derived neurotrophic factor (MANF) that bind KDELR itself on the plasma membrane [ 58 , 59 ].…”
Section: Involvement Of Kdelrs In Human Diseasesmentioning
confidence: 99%
“…For glial cells, autophagy is associated with the immune response by regulating microglial phagocytosis and microglial polarization by enhancing the conversion from M1 (pro‐inflammation) to M2 (anti‐inflammation) phenotype (Jin et al, 2018; Su et al, 2016). In neurons, autophagy participates in neuronal physiology by regulating neuronal plasticity, dendritic spine formation and axonal development (Valencia et al, 2021). Typically, the autophagic process is mostly induced by the activation of AMP‐activated protein kinase (AMPK) pathway and by the inhibition of the nutrient starvation‐mediated mammalian target of rapamycin complex 1 (mTORC1) pathway.…”
Section: Current Concepts Of Molecular Mechanisms and Potential Thera...mentioning
confidence: 99%